An Observational Study to Assess Smartphone Usage in Patients of Anxiety and Depression - Aditya Satish Nair; Ankit Halder; Roma Shahani; Nikhil Avula; Devavrat Harshe; Gurudas Harshe (Annals of Indian Psychiatry)
Background: Anxiety and depression disorders are among the most common psychiatric illness in the community and primary care. There is paucity in data regarding the assessment of smartphone use in mental disorders. Therefore, the study was undertaken to assess the use of smartphones at the time of presentation at a tertiary care centre and after an episode of anxiety and/or depression. Methodology: 145 subjects were screened for depression and anxiety subjectively. Smartphone use was assessed at the time of diagnosis, and for 1 week, 5 weeks and 3 months by using Stay Free© App. Results: There was significant correlation between total screen time with HAM D and HAM A scores. Conclusion: Smartphone usage is significantly associated with severity of depression and anxiety. Counselling of the subjects with anxiety and depression regarding the effect of smartphones on health is required and instructions should be given regarding the proper use of gadgets.